Controles biofísicos sobre a evapotranspiração e eficiência do uso da água em área alagável no Norte do Pantanal Mato-grossense - Silva, Jonh Billy da (2023)
The Brazilian Pantanal is the largest seasonal wetland in the world with a landscape composed of a mosaic of temporary and permanent aquatic habitats, forests, and flooded and non-flooded grasslands. However, the energy exchange patterns are not entirely understood, especially for seasonally flooded forests. Thus, the main objective of this research was to evaluate the variability of evapotranspiration () and its biophysical controls, as well as, to analyze the energy partitioning and water use efficiency () for a seasonally flooded forest of the North of Mato Grosso Pantanal. The Eddy Covariance system was used to measure latent () and sensitive () heat flows in conjunction with micrometeorological and remote sensing data to evaluate the connection between water dynamics and phenology. Our data suggest that 72% of liquid radiation () was consumed by + , even during the dry period, with the closure of the energy balance () of 0,91 ± 0,29 by the fraction, indicating that trees can access deep water when surface water is limited. and were higher during the wet season, 18% and 16% respectively. The interannual decoupling factor (0,63 ± 0,04) and the interannual Priestley-Taylor coefficient () (0,86 ± 0,21), suggests that the canopy is decoupled from the atmosphere and is essentially sensitive to . patterns and vapor pressure deficit () suggest that was more dependent on incoming and less dependent on stomatic control, but still exhibited a strong relationship with biotic factors, such as the enhanced vegetation index (), which is sensitive to seasonal variations in leafy area and canopy cover index. The efficiency of water use () during the study period showed high seasonality, with higher values during the wet season and interannual average of 0,57±0,26 (gC kg-1 H2O-1 ), with a strong negative correlation with the net exchange of CO2 by the ecosystem () ( = −0,934;p < 0,01). There has been a reduction in the average and hourly values of over the years, a behavior that can be explained by the occurrence of more intense droughts happening in the region of the Pantanal Mato-grossense in recent years. These data indicate that seasonally flooded forests, such as the Pantanal in the Mato Grosso, are consistent sources of water vapor for the atmosphere even during seasonal drought.